RNAi inhibition of angiopoietin-like protein 3 (ANGPTL3) with ARO-ANG3 mimics the lipid and lipoprotein profile of familial combined hypolipidemia. (25th November 2020) - Watts, G.F; Schwabe, C; Scott, R; Gladding, P; Sullivan, D; Baker, J; Clifton, P; Hamilton, J; Given, B; San Martin, J; Melquist, S; Knowles, J.W; et al.
Abstract: Background: Elevated LDL-C and triglyceride rich lipoproteins (TRLs) are independent risk factors for cardiovascular disease (CVD). Genetic deficiency of angiopoietin-like protein 3 (ANGPTL3) is associated with reduced circulating levels of LDL-C, triglycerides (TGs), VLDL-C, HDL-C and reduced CVD risk, with no described adverse phenotype. ARO-ANG3 is a RNA interference drug designed to silence expression of ANGPTL3. Single doses of ARO-ANG3 have been shown to reduce ANGPTL3, TGs, VLDL-C and LDL-C in healthy volunteers (HVs, AHA 2019). We report the effects of multiple doses of ARO-ANG3 in HVs with a focus on the duration of action. Methods: ARO-ANG3 was administered subcutaneously to HVs on days 1 and 29 at doses of 100, 200 or 300 mg (n=4 per group). Measured parameters included ANGPTL3, LDL-C, TGs, VLDL-C and HDL-C. Follow up is ongoing. Results: All HVs have received both doses and follow-up is currently through week 16 (12 weeks after second dose). Mean nadir for ANGPTL3 levels occurred 2 weeks after the second dose (−83–93%) with minimal change for 200 and 300 mg but 16% recovery for 100 mg at week 16. Mean TGs and VLDL-C reached nadir earlier (3 wks, −61–65%) without apparent dose response and minimal change for any dose at wk 16. LDL-C nadir occurred 4–6 wks after the second dose (−45–54%), again with minimal evidence for dose response or change through wk 16. HDL-C was reduced 14–37% at wk 16. ARO-ANG3 was well tolerated without serious or severe adverse events or dropouts related to drug. The most common adverse events have been headache and upper respiratory infections. Conclusions: Genetic deficiency of ANGPTL3 is a cause of familial combined hypolipemia and is associated with a decreased risk of CVD. Using RNAi to selectively suppress ANGPTL3 production reproduces these genetic effects with a duration of at least 12 weeks following a second dose and with good tolerability over 16 wks. ANGPTL3 inhibition results in lowering of LDL-C and TRLs which may confer protection against CVD in patients with atherogenic mixed dyslipidemia. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Arrowhead Pharmaceuticals